Genomic predictors of remission to antidepressant treatment in geriatric depression using genome‐wide expression analyses: a pilot study. (15th October 2015) - Eyre, Harris A.; Eskin, Ascia; Nelson, Stanley F.; St. Cyr, Natalie M.; Siddarth, Prabha; Baune, Bernhard T.; Lavretsky, Helen
Abstract : Objective: This first pilot study of genome‐wide expression as predictor of antidepressant response in late‐life depression examined genome‐wide transcriptional profiles in a randomized placebo‐controlled trial of combined methylphenidate and citalopram. Methods: Genome‐wide transcriptional profiles were examined in peripheral blood leukocytes sampled at baseline and 16 weeks from 35 older adults with major depression, who were randomized to methylphenidate + citalopram, citalopram + placebo, or methylphenidate + placebo. Methylphenidate doses ranged between 10 and 40 mg/day, and citalopram doses ranged between 20 and 60 mg/day. Remission was defined as Hamilton Depression Rating Scale score of 6 or below. Early remission was achieved in the first 4 weeks of treatment. We hypothesized that differential gene expression at baseline can predict antidepressant response. Results: We analyzed gene expression in 24 remitters and 11 non‐remitters. At baseline, we found three genes showing higher expression in all remitters versus non‐remitters that satisfied the established level of significance: a fold change of 2 and p ‐value of 0.05 that included HLA‐DRB5, SELENBP1, and LOC388588. Two gene transcripts showed higher expression in early remitters at baseline compared with non‐remitters. The first gene was CA1 carbonic anhydrase gene, on chromosome 8 involved in respiratory function (fold change 2.54; p = 0.03). The second gene was the SNCA‐α‐synuclein gene, implicated, which binds to dopamine transporter (fold change 2.1; p = 0.03). Conclusions: Remission to antidepressants in geriatric depression may be associated with a particular gene expression profile in monoaminergic and metabolic pathways and needs to be replicated in a larger sample. Copyright © 2015 John Wiley & Sons, Ltd.